Kolizyjnoprawne aspekty małżeństw dzieci - Kamarad, Ewa (Problemy Prawa Prywatnego Międzynarodowego, 2019)
In the Western culture there is a widespread belief that marriage should be contracted only by freely expressed will. Hence, marriages concluded at an early age are considered unacceptable. Entering into marriage by children has a negative impact on their education, physical and mental health, as well as their socioeconomic position. For this reason, such practices are incompatible with human rights. Therefore, European countries are trying to counteract them, which results in taking specific legislative actions. The intensification of these activities is particularly evident in the last decade, which is mainly caused by the increased migration to Europe from countries belonging to other cultural circles. Child marriages, being a phenomenon strongly embedded in culture, have become one of the areas where there are frictions between the majority, which in principle determines the shape of legal regulations, and minorities who, on the one hand, want to live in European countries, but also want to preserve the traditions that are cultivated in their countries of origin. The changes in law considering child marriages are undertaken in realm of substantive law as well as conflict of laws rules. In the second case, the states introduce specific public policy clauses referring to child marriages. The paper aims at describing and evaluating those changes in law, especially from the point of view of private international law.